The Effect of Two Stay-Two Stray Cooperative Learning Methods and Think Pair Share on Student Learning Outcomes of Geography - Arif Srirahmad Isnain; Benedict Arko (Journal of Social Knowledge Education (JSKE), 2023)
The purpose of this study was to find out: 1) differences in student learning outcomes of Geography after using the Two Stay Two Stray, Think Pair Share and Discussion learning methods. 2) differences in Geography learning outcomes for students after using the Two Stay Two Stray and Discussion learning methods. 3) differences in student learning outcomes of Geography after using the Think Pair Share learning method with Discussion. 4) differences in student learning outcomes of Geography after using the Two Stay Two Stray and Think Pair Share learning methods in (material Distribution of Natural Disaster Prone Areas in Indonesia) class X IPS SMA Negeri 1 Sukoharjo Academic Year 2015/2016. This study uses a Quasi-Experimental research method with the design "Postest-Only Control Group Design". The population in this study were all class X social studies students at SMA Negeri 1 Sukoharjo in the 2015/2016 academic year. Samples were taken using the Cluster Random Sampling technique. The selected sample is class X IPS 2, X IPS 3 and X IPS 4. The technique of collecting data on learning outcomes uses a test technique in the form of essay questions. The data analysis technique used was One Way Anava and post Anava test (Scheffe' method) with a significance level of 5%. The results of the study show that: (1) there are differences in the learning outcomes of Geography students who use the Two Stay Two Stray, Think Pair Share, and Discussion learning methods with the acquisition of Fobs > Fα scores; (2) the learning outcomes of Geography using the Two Stay Two Stray learning method are better than the Discussion learning method; (3) the learning outcomes of Geography using the Think Pair Share learning method are better than the Discussion learning method; (4) the learning outcomes of Geography using the Two Stay Two Stray learning method are better than the Think Pair Share learning method. Based on these data, it can be seen that the learning method that has the greatest influence is the Two Stay Two Stray method, followed by the Think Pair Share method, and the Discussion method.